1971
DOI: 10.1136/jcp.24.6.533
|View full text |Cite
|
Sign up to set email alerts
|

A micro-method for peripheral leucocyte migration in tuberculin sensitivity

Abstract: (Dumonde, 1970). The ability of these soluble factors to inhibit the migration of cultured macrophages and leucocytes provides one measure ofcellular hypersensitivity (see Dumonde and Maini, 1971). In this paper we describe an improved method for detecting the inhibition of leucocyte migration by specific antigen which is based on the technique of Bendixen and S0borg (1969 90 min in a non-wettable plastic sterile test tube, by which time the red cells had settled at the bottom, leaving a leucocyte-rich plasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

1972
1972
1981
1981

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(34 citation statements)
references
References 9 publications
1
32
0
1
Order By: Relevance
“…The method used for leucocyte migration was similar to that of Federlin et al (1971) In a small number of cases, parallel studies were performed using a guinea-pig macrophage migration test (MMT) similar to that employed by Rajapakse and Glynn (1970). Guinea-pig macrophages were obtained as peritoneal exudates 3 days after the intraperitoneal injection of 20 ml sterile liquid paraffin, and were washed 3 times in medium 199.…”
mentioning
confidence: 99%
“…The method used for leucocyte migration was similar to that of Federlin et al (1971) In a small number of cases, parallel studies were performed using a guinea-pig macrophage migration test (MMT) similar to that employed by Rajapakse and Glynn (1970). Guinea-pig macrophages were obtained as peritoneal exudates 3 days after the intraperitoneal injection of 20 ml sterile liquid paraffin, and were washed 3 times in medium 199.…”
mentioning
confidence: 99%
“…Soborg [55] claimed that stimulation might be considered to be very similar to inhibition, in that it reflects weak sensitization. Other workers, using peripheral blood leucocyte migration, have concluded that stimulation reflects a state of delayed hypersensitivity [12,18,54]. This phenomenon is also described when using guinea-pig peritoneal exudate cells as target.…”
Section: Migration Stimulationmentioning
confidence: 76%
“…S0borg [55] used leucocyte migration as an indication of delayed hypersensitivity, and together with others [12,18,54] accepts that stimulation of migration represents weak sensitization. This would fit in with the concept of active suppression and the production of M.St.F.…”
Section: Clinical Observations With Mstfmentioning
confidence: 99%
“…Furthermore, a range of nega tive and positive results were obtained in both these tests on each occa sion and neither test showed an overall depression on any day. It should also be noted that the PPD concentrations used here for LMI are lower than those employed by some authors [27][28][29]. However, the concentra tion range employed in this study was chosen after exhaustive preliminary experiments over a wider concentration range and were shown to elicit maximal responses in the majority of subjects.…”
Section: Variability Within Individual In Vitro Lftsmentioning
confidence: 99%